Avaliação de uma unidade de negócio de base tecnológica pelo valor justo com base na abordagem da receita : comparação entre valor presente e precificação de opções - Oshita, Marcela Gimenes Bera (2016)
Assets based on knowledge whose fair value is not observable in the market is indicated to be evaluated by the approach of the recipe, just use techniques based on discounted cash flows, which convert future amounts to a single current value. The techniques may be the present value or pricing for options, and your choice is a decision of the administration, the first technique the most widespread. The pricing of options was based on the Theory of Real Options. This study aims to compare, through simulation, technical present value and option pricing for valuation at fair value of a business unit of technological base. The simulation followed some steps: projection of cash flow; calculation of the risk-free rate; discounted cash flows to present value; estimation of uncertainty of cash flows; application of binomial model; analysis of real options and; the comparison of results through the technical present value and option pricing, through the lens of accounting theory. The results showed that the present value is a valid technique for evaluation of technology-based assets and real options can be a complementary technique, when there is no occurrence of uncertainties and risks. When uncertainties and risks are important factors real options becomes a more robust technique, because it allows the development of scenarios and the insertion of managerial flexibility. The main conclusion indicates that both techniques are suitable for measuring the fair value of an asset when it adopts the approach of the recipe and techniques that are based on the discounted cash flow. The choice of one of them, the accounting practice, should consider the circumstances inherent in active evaluation and the availability and quality of data. The main contribution of this research was to compare two techniques (present value and real options) and although provided for in CPC 46, the pricing of options is little discussed in accounting. The comparison of the values possible to identify the generation of the flexibility value for interested parties to have more confidence when using the techniques based on discounted cash flows to evaluate technology-based assets.